Alcohol abstinence vs. persistent alcohol consumption in alcoholic cardiomyopathy: impact on long-term prognosis. (3rd October 2022) - Cediel Calderon, G; Lopez, H; Domingo, M; Codina, P; Santiago, E; Borrellas, A; Gonzalez, B; Rivas, C; Crespo, E; Pulido, A; Velayos, P; Barcelo, E; et al.
Abstract: Background: Alcoholic Cardiomyopathy (ACM) remains a prevalent form of toxic-induced heart damage. Whether ACM prognosis depends on the persistence of alcohol consumption is a matter of debate. Purpose: We sought to determine predictors of adverse events during long-term follow-up and left ventricular ejection fraction (LVEF) changes between abstainers and non-abstainers. Methods: Consecutive patients admitted to a HF clinic from 2001 to 2020 with ACM were included. The primary endpoint was the composite of all-cause death or HF hospitalization. HF hospitalization was analyzed as a secondary outcome. Changes in LVEF at 1- and 3-years follow-up according to discontinuation of alcohol consumption was also analyzed. Multivariable Cox regression analyses were performed using the competing risk strategy for the secondary endpoint. Results: A total of 122 patients were included with a mean age of 57.8±10.0 years and 95.1% (n=116) of males. The mean LVEF was 27.5% ± 10.6 and 11.5% (n=14) exhibited NYHA functional class 3. A total of 92 (75.4%) patients remained abstinent during follow-up; the rest continued with at least moderate alcohol intake. After a median follow-up of 6.8 years (interquartile range: 3.2 to 11.3 years), 59 (48.4%) presented the primary endpoint (45 [36.9%] died and 34 [27.9%] experienced HF readmission). Independent predictors of the primary outcome were age (hazard ratio [HR]: 1.03; 95% confidence interval [CI]: 1.00–1.06; p=0.042), hemoglobin (HR: 0.68; 95% CI: 0.56–0.82; p<0.001) and alcohol abstinence (HR: 0.35; 95% CI: 0.20–0.61; p<0.001). Predictors of HF readmission were hemoglobin (HR: 0.65; 95% CI: 0.50–0.83; p=0.001) and alcohol abstinence (HR: 0.39; 95% CI: 0.17–0.92; p=0.032). Improvement in LVEF was higher in abstainers (27.5±10.6% from baseline to 46.7±13.1% and 49.1±14.3% at 1- and 3-years respectively) than in non-abstainers (27.8±10.3% to 40.3±14.0% and 39.2±16.3% at 1- and 3-years respectively), being these changes in LVEF significantly different between both groups (p=0.004). Conclusions: Patients with ACM and who remain abstainers during follow-up exhibit better outcomes and higher LVEF improvement in comparison to non-abstainers. These findings should help to inform lifestyle modification for patients with ACM. Funding Acknowledgement: Type of funding sources: None.